Changes Physical Activities of Daily Living Elderly Individuals Involved in Interdisciplinary Care - Wantonoro; Sugiantoro, Hari Akbar; Nguyen, Tuan Van (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The populations of all countries, including Indonesia, are aging, leading to an increasing elderly population with a greater number of health issues and comorbidities. The aim was to determine whether involvement in an interdisciplinary care program can help elderly individuals maintain physical activities of daily living. This was a quantitative longitudinal study with a quasiexperimental one-group pretest–posttest design. Fifteen participants were included, and one participant died before the 6-month follow-up. The Indonesian version of the Barthel Index was used to measure physical activities of daily living (PADLs) before and at one, three and six months after the intervention. Linear regression models using the generalized estimating equation approach were used to determine significant PADLs changes and predictive factors. The mean total PADL score at T1, T2 and T3 increased significantly compared to that at T0 (p<.001). Age (β=-0.33; p=.001), diabetes mellitus (β=-2.16; p=.001), stroke (β=-5.78; p=.001) and congestive heart failure (β=-10.68; p=.001) were the strongest predictors of PADLs. Interdisciplinary team care may help elderly individuals maintain PADLs. The risk factors for PADLs deterioration were older age and comorbidities, including diabetes mellitus, stroke and heart failure. A subsequent investigation of homogeneous participants with a control group is suggested for future studies.